Increasing corrosion resistance of binary Al-Alloy through implanting with some transition elements and heteroatom organic compounds - Fatemeh Mollaamin (Acta Chimica Asiana, 2023)
Decorating of Transition metals (TMs) on the "AlMg" nanoalloy has been studied on the basis of Langmuir adsorption applying "ONIOM" model with three levels of «high, medium and low» by using "LANL2DZ /6-31+G(d,p)/EPR-III", "semi-empirical" and "MM2" functions. The fluctuation of "NQR" has estimated the inhibiting role of pyridine and alkylpyridines containing 2-picoline (2Pic), 3-picoline (3Pic) ,4-picoline (4Pic), and 2,4-lutidine (24Lut) for (Sc, Ti, Cr, Ni, Cu, Zn)-doped AlMg alloy nanosheet due to "N" atom in the benzene cycle of heterocyclic carbenes being near the monolayer surface of ternary "TM–(Al–Mg)" (TM= Sc, Ti, Cr, Ni, Cu, Zn) nanoalloys. The "NMR" spectroscopy has remarked In fact, the NMR results of the adsorption of pyridine and alkylpyridines of 2Pic, 3Pic, 4Pic and 24Lut molecules represent spin polarization on the TM (Sc, Ti, Cr, Ni, Cu, Zn)-doped Al–Mg nanoalloy surfaces that these surfaces can be employed as the magnetic N-heterocyclic carbene sensors. In fact, "TM" sites in "TM–(Al–Mg)" nanoalloy surfaces have bigger interaction energy amount from "Van der Waals’ forces" with pyridine and its nitrogen heterocyclic family that might cause them large stable towards coating data on the nanosurface. It has been estimated that the criterion for choosing the surface linkage of "N" atom in pyridine and alkylpyridines in adsorption sites can be impacted by the existence of close atoms of aluminum and magnesium in the "TM–(AlMg)" surfaces. Moreover, "IR" spectroscopy has exhibited that (Sc, Ti, Cr, Ni, Cu, Zn)-doped AlMg alloy nanosheet with the fluctuation in the frequency of intra-atomic interaction leads us to the most considerable influence in the vicinage elements generated due to inter-atomic interaction. Comparison to amounts versus dipole moment has illustrated a proper accord among measured parameters based on the rightness of the chosen isotherm for the adsorption steps of the formation of Py@Sc–(Al–Mg), Py@Ti–(Al–Mg), Py@Cr–(Al–Mg), Py@Ni–(Al–Mg), Py@Cu–(Al–Mg), and Py@Zn–(Al–Mg) complexes. Thus, the interval between nitrogen atom in pyridine during interaction with transition metals of "Sc, Ti, Cr, Ni, Cu, Zn" in "TM–(Al–Mg)" nanoalloys, (N→TM), has been estimated with relation coefficient of R² = 0.9284. Thus, the present has exhibit the influence of "TMs" doped on the "Al–Mg" surface for adsorption of N-heterocyclic carbenes of pyridine and alkylpyridines by using theoretical methods.